Spatial Information Research - Spatial Information Research (Springer Nature, 2026)
Spatial Information Research is an international interdisciplinary journal that publishes high-quality research articles in spatial information science. Covers technology, policy, and practice in the field of spatial information science. Explores both operational and computational issues of spatial information. Mixes academia and industry for a unique perspective on Spatial Information Science. Publishes a variety of article types, including original research articles, reviews and special case reports. Official journal of the Korea Spatial Information Society
FI 0.39
Q3
Keywords: Earth; Space & Environmental Sciences; Cartography; Cartografía; Acuerdos transformativos; Transformative agreements; Ciencia de la información espacial; Sistemas de Información Geográfica; Fotogrametría